Level of digital citizenship among Palestinian university students (Journal of the College of Education for Women, 2025)
The study aims to identify the level of agreement in using English as a medium of instruction according to study sample responses to the Context, Input, Process, and Product model questionnaire and evaluate the English as a medium of instruction program in secondary schools for distinguished students by the study sample according to the CIPP questionnaire items. The descriptive quantitative study included 109 teachers who actively attended the program in Iraq during the 2023–2024 academic year. To achieve the aims of this study, a five-point Likert scale questionnaire with 47 items based on Stufflebeam's (2015) CIPP model was prepared, validated, and administered to the participants in person and online. The data has been analyzed using SPSS. The findings have revealed that the teachers generally evaluated many aspects of the program positively. For example, the context of the course book prepares students scientifically and linguistically for their future. However, the study also revealed that (EMI) implementation poses challenges for teachers and students, including the absence of specific guidelines for EMI implementation and teachers' in-service training.